Racism, Sexism and the Genesis of a “Womanish” Identity in Selected Novels by Alice Walker and Toni Morrison - CHOUCHANE, Selma (Journal of Human Sciences, 2019)
This article explores the genesis of a new meaning of black womanhood in Toni Morrison’s The Bluest Eye and Sula and Alice Walker’s The Color Purple and Possessing the Secret of Joy. The four novels examine how racism and sexism define black women’s gender roles, categorize their beauty and mutilate their sexuality. However, both Morrison and Walker witnessed the genesis of a “womanish” identity which is primarily based on woman’s strength, love, and survival. Alice Walker’s Womanism is adopted as the basic analytical method. As a literary movement, Womanism tries to give black women the voice of liberty, empowerment, and equality in order to fight both race and gender prejudice.